NAMPT/SIRT1 Attenuate Ang II-Induced Vascular Remodeling and Vulnerability to Hypertension by Inhibiting the ROS/MAPK Pathway. (31st December 2020) - Zhou, Lei; Zhang, Sheng; Bolor-Erdene, Enkhbat; Wang, Lingwei; Tian, Ding; Mei, Yunqing
Abstract : Hypertension is characterized by endothelial dysfunction, vascular remodeling, and rearrangement of the extracellular matrix. Besides, the pathogenesis of hypertension is closely related to excess generation of reactive oxygen species (ROS). Nicotinamide phosphoribosyltransferase (NAMPT) is a rate-limiting enzyme in nicotinamide adenine dinucleotide (NAD) biosynthesis that influences the activity of NAD-dependent enzymes, such as sirtuins, which possess NAD-dependent protein deacetylase activity and cleave NAD during the deacetylation cycle. Recently, NAMPT has been shown to play a crucial role in various diseases associated with oxidative stress. However, the function and regulation of NAMPT in hypertension have not been extensively explored. In the present study, we identified NAMPT as a crucial regulator of hypertension, because NAMPT expression was significantly downregulated in both patients with hypertension and experimental animals. NAMPT knockout (NAMPT+/-) mice exhibited a significantly higher blood pressure and ROS levels after stimulation with angiotensin II (Ang II) than wild-type mice, and the administration of recombinant human NAMPT (rhNAMPT) reversed this effect. In vivo, overexpression of NAMPT protected against angiotensin II- (Ang II-) induced hypertension by inhibiting ROS production via sirtuin 1 in mouse aortic endothelial cells (MAECs) and mouse aortic vascular smooth muscle cells (MOVAs). In turn, NAMPT alleviated the ROS-induced mitogen-activated protein kinase (MAPK) pathway. In conclusion, NAMPT might be a novel biomarker and a therapeutic target in hypertension.